Oil Spill Pollution Detection Using Palsar Data In Timor Sea - Tri Muji Susantoro; Suliantara Suliantara; Djoko Sunardjanto (Scientific Contributions Oil and Gas, 2010)
The processing of Palsar imagery has been conducted for detecting an oil spill in Timor Sea. Three series of Palsar imageries i.e. Sept 2nd, Oct 3rd and Oct 6th, 2009 are used to analysis in this area. At September 2nd, 2009 based on Palsar Imagery, oil spill was detected around of Montara Platform. Oil spill seen appeared as dark tone The area that has been covered by oil spill is more than 100 km2. At September 24rd, 2009 oil spill was dispersed to North and West Montara Field. At October 3, 2009 showed that oil spill was detected in the north of Seba Coast, Sawu Island. Oil spill in this area clearly showed in Palsar Imagery base on a long dark lines. Oil spill at October 6th, 2009 were still dispersed in Timor Sea. Based on Palsar imagery, oil spill is identified in South Rote Island about 150 km long, appeared as dark lines in Palsar imagery